Feasibility of Home Industries Chips Skin Catfish Brand: Case Study at UD. Sumber Rejeki Blitar - Fatmawati, Erlin Widya (Prosiding Seminar, 2020)
The purpose of this study are to find out the extent of marketing mix that has been carried out and to find out the feasibility of the product Chips Skin Catfish brand â€œMboâ€™dheâ€ at UD. Sumber Rejeki. The research used qualitative method with case study approach. Data collection: interviews, observation techniques and documentation. Data analysis, namely data reduction, data display and conclusion drawing / verification. Research results has conducted a Marketing Strategy which includes marketing mix of 4P (Product, Price, Place, and Promotion) and STP (Segmentation, Targeting, and Positioning). Analysis Feasibility on subject with product Chips Skin of Catfish has reached BEP and is feasible to continue to run in the future. This study recommended to provide benefits and advice for home industries that are still developing and require targeted marketing strategies